Preterm Prelabor Rupture of Membranes between 34 and 37 Weeks: A Point-of-Care Test of Vaginal Fluid Interleukin-6 Concentrations for a Noninvasive Detection of Intra-Amniotic Inflammation - Kacerovsky, Marian; Musilova, Ivana; Bestvina, Tomas; Stepan, Martin; Cobo, Teresa; Jacobsson, Bo (Fetal diagnosis and therapy, 2018)
OBJECTIVE: The aim of this study was to investigate whether a previously reported vaginal fluid point-of-care interleukin (IL)-6 cut-off value of 2,500 pg/mL can be used for the identification intra-amniotic inflammation in women with preterm prelabor rupture of membranes (PPROM) between 34 and 37 weeks. MATERIAL AND METHODS: A prospective cohort study was conducted in women with singleton gestation complicated by PPROM between 34 + 0 and 36 + 6 weeks. Vaginal fluid was successfully obtained in 118 women from the posterior vaginal fornix via aspiration using a sterile urine sample tube with a suction tip. Amniotic fluid was obtained via transabdominal amniocentesis. IL-6 concentrations were assessed in both fluids immediately after sampling. Intra-amniotic inflammation was defined as an amniotic fluid point-of-care IL-6 concentration of ≥745 pg/mL. RESULTS: The tested vaginal fluid IL-6 cut-off value had a sensitivity of 91%, specificity of 91%, positive predictive value of 50%, negative predictive value of 99%, positive likelihood ratio of 9.7, and negative likelihood ratio of 0.1 for the identification of intra-amniotic inflammation. CONCLUSION: The point-of-care vaginal fluid IL-6 test with a cut-off value of 2,500 pg/mL shows good sensitivity, specificity, and negative predictive value for the identification of intra-amniotic inflammation in PPROM between 34 and 37 weeks.
Keywords: dospělí; Late PPROM; Female; předčasný odtok plodové vody; novorozenec; Adult; mladý dospělý; ženské pohlaví; Vagina; lidé; Infant, Newborn; infekce; těhotenství; Interleukin-6; Infections; Amniotic fluid; Point-of-Care Testing; Rapid test; Fetal Membranes, Premature Rupture; Microbial invasion of the amniotic cavity; prospektivní studie; Noninvasive procedure; Prospective Studies; point of care testing; Intra-amniotic inflammation; Lateral flow-based immunoassay; Young Adult; interleukin-6; nemoci novorozenců; Pregnancy; Preterm delivery; Cytokine; Infant, Newborn, Diseases; vagina; Humans